2015
DOI: 10.13080/z-a.2015.102.010
|View full text |Cite
|
Sign up to set email alerts
|

Plum (Prunus spp.) aphid guild (Hemiptera: Sternorrhyncha, Aphididae) structure in Lithuania: any impact of an alien aphid species?

Abstract: A comparison of the plum aphid (Hemiptera: Aphididae) guild structure in Lithuania before (1975) and after (2012) the establishment of the invasive aphid species Brachycaudus divaricatae Shaposhnikov, 1956, was performed to investigate the impact of this invasive species on the native species complex. No substantial changes in the native plum aphid species composition, host plant associations and seasonal frequency dynamics were detected. The incorporation of B. divaricatae into the plum aphid guild in the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On the molecular level, these populations of B. divaricatae appeared to be extremely monomorphic in their partial sequences of mitochondrial COI and nuclear EF-1α genes (BAŠILOVA et al 2012). The most recent studies have revealed that, despite population outbreaks, B. divaricatae did not have any distinct negative effect on the plum aphid guild structure in Lithuania (RAKAUSKAS et al 2015b). This is partially explainable by the ability of the local ladybird species to prey on B. divaricatae (DANILOV & RAKAUSKAS unpublished).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the molecular level, these populations of B. divaricatae appeared to be extremely monomorphic in their partial sequences of mitochondrial COI and nuclear EF-1α genes (BAŠILOVA et al 2012). The most recent studies have revealed that, despite population outbreaks, B. divaricatae did not have any distinct negative effect on the plum aphid guild structure in Lithuania (RAKAUSKAS et al 2015b). This is partially explainable by the ability of the local ladybird species to prey on B. divaricatae (DANILOV & RAKAUSKAS unpublished).…”
Section: Resultsmentioning
confidence: 99%
“…Particular emphasis is placed on characteristics that differing from what is commonly known about these species (BLACKMAN & EASTOP 2000). (RAKAUSKAS 1978, 1980, 1983a, RAKAUSKAS et al 2015b.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, aphids are particularly good models for invasion studies because they possess many biological characteristics favouring their success in establishing new populations, such as parthenogenetic reproduction, short generation times, and high dispersal capacity (Dixon 1998). High availability of winter host plant together with low abundance of other aphid species on cherry plums (Rakauskas et al 2015) enabled B. divaricatae to reach the northern edge of the invasive distribution area of P . cerasifera, its winter host, in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Hałaj and Osiadacz 2015, Martin 2010, Osiadacz and Hałaj 2014, Vučetić et al 2014) and alien (e.g. Coeur d'acier et al 2010, Hałaj et al 2011, Pérez Hidalgo and Mier Durante 2012, Rakauskas et al 2015) -expanding their distribution ranges in Europe. Cinara curvipes (Patch) -the bow-legged fir aphid -is one such alien species, originally from North America, where it is widespread (Maw et al 2000;Voegtlin and Bridges 1988).…”
Section: Introductionmentioning
confidence: 99%